Estudio del manejo interno de los residuos sólidos domésticos generados en el puerto pesquero La Pitahaya del cantón Arenillas, provincia de El Oro. 2014 - Benavidez Tirado, Gina Lissbeth (2014)
To perform this study was planned as targets to determine the internal management of domestic solid waste generated by residents of Puerto Pesquero Pitahaya, with different methods and research techniques in order to identify the types of solid waste generated in homes, also verify the existence of visual impact caused by inadequate internal management of domestic solid waste to establish alternative solutions to the problem.